Cyclic Mechanical Stretch Ameliorates the Degeneration of Nucleus Pulposus Cells through Promoting the ITGA2/PI3K/AKT Signaling Pathway. (17th March 2021) - Wang, Dandan; Chen, Yuanzhen; Cao, Shengnan; Ren, Pengcheng; Shi, Haojun; Li, Huazhong; Xie, Liangyu; Huang, Weimin; Shi, Bin; Han, Jinxiang
Abstract : Background . Intervertebral disc degeneration (IVDD) is one of the major causes of low back pain and motor deficiency. Nucleus pulposus (NP) degeneration plays a key role in the process of IVDD. The mechanical and biological interactions involved in NP degeneration have not been elucidated. The present study is aimed at investigating the effect and mechanism of cyclic mechanical stretch in regulating the function and degeneration of NP cells. Methods . NP cells were subjected to cyclic tensile stress (10% deformation) of 0.1 Hz for 8640 cycles. Cell proliferation was conducted through the MTT assay. The cell cycle and apoptosis were detected by flow cytometry. A gene expression profile chip was used to analyze the differentially expressed genes between the tensile stress group and the control group. Enrichment analysis of Gene Ontology (GO) annotation and signaling pathways were analyzed. Western blot and RNA interference were carried out to investigate the role of the ITGA2/PI3K/AKT pathway in the effect of cyclic mechanical stretch on NP cells. Results . NP cells exhibited a greater (P < 0.05 ) growth rate in the tensile stress group compared to the control group. Cyclic mechanical stress significantly promoted the cell cycle transition of NP cells from the S phase to the G2/M phase. A fewer proportion of apoptotic cells were found in the tensile stress group (P < 0.05 ), indicating that cyclic mechanical stretch inhibits NP cell apoptosis. Microarray analysis revealed 689 significant differentially expressed genes between the two groups (P < 0.05 ), of which 333 genes were upregulated and another 356 genes were downregulated. Cyclic mechanical stretch altered the expression of 31 genes involved in the ITGA2/PI3K/AKT pathway and remarkably promoted this pathway in NP cells. Downregulation of ITGA2 and AKT further demonstrated that the PI3K/AKT pathway was responsible for the proliferation and COL2A1 expression of NP cells upon cyclic mechanical stretch. Conclusions . Cyclic mechanical stretch promoted the proliferation and cell cycle and reversely inhibited the apoptosis of NP cells. Cyclic mechanical stretch promoted COL2A1 expression and ameliorated the degeneration of NP cells via regulation of the ITGA2/PI3K/AKT signaling pathway. Our results may provide a potential target and a possibility of IVDD disease treatment by ameliorating the degenerative changes.